Advanced skills : a resource book of advanced-level skills activities. - Haines, Simon F. E., ....- (Cambridge : University Press, 2006)
Advanced Skills completes the Listening/Speaking/Reading/Writing Extra suite of books by offering extra skills practice at advanced level. While not specifically written as exam practice material, the book includes tasks similar to those that students have to do in the main Cambridge exams (CAE, CPE, IELTS). The book is divided into four sections by skill and each section offers nine units on the same nine general topics. Each activity includes a page of step-by-step teacherÂ's notes and one to three photocopiable pages for students to use in class. The lessons last approximately 60 minutes. Each activity focuses on a particular skill, for example, listening for specific information, but students will also use other skill areas, such as speaking and writing, as part of the lesson. The book explores topics such as relationships, emotions, rights and wrongs and the unexpected, approaching these topics from original angles, which will capture the interest of students.
Keywords: Engels -- Taalgebruik